Information from sound: exploring sounds and listening in information practices research - Stewart-Robertson, Owen (Information Research an international electronic journal, 2024)
Introduction. This conceptual paper discusses the possibilities for expanding research around sounds/listening and sound-related practices in information research to further understandings of embodied/sensory information practices and attend to a greater diversity of information experiences and ways of knowing. Method/Analysis. The growth of research related to broad conceptualisations of sound and listening and the use of information from sound in knowledge production across many fields is discussed. Some challenges faced by that research and gaps in existing sound-related information practices research are noted. Results. Sound research in other fields faces issues around the management, interpretation, and contextualisation of sound-related data, and little is understood about the practices of sound recordists. Some information practices-related research has highlighted the complexity of interactions with sounds and related technologies and explored interactions with oral and music information sources. However, experiences and perceptions around seeking, creating, and using information from sounds lack in-depth study. Conclusion. The value of further information practices research related to sound is suggested: to expand embodied/sensory information research, to engage with the broad range of sonic skills and experiences, to further holistic examinations of information interactions, and to address information-related problems and research gaps in sound-focused research from other fields.